2018
DOI: 10.1107/s2053273317014929
|View full text |Cite
|
Sign up to set email alerts
|

The limit of application of the Scherrer equation

Abstract: The Scherrer equation is a widely used tool to obtain crystallite size from polycrystalline samples. Its limit of applicability has been determined recently, using computer simulations, for a few structures and it was proposed that it is directly dependent on the linear absorption coefficient (μ) and Bragg angle (θ). In this work, a systematic study of the Scherrer limit is presented, where it is shown that it is equal to approximately 11.9% of the extinction length. It is also shown that absorption imposes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 22 publications
4
70
0
Order By: Relevance
“…A narrower half‐breadth at 2 θ = 20° could be observed in diffraction spectrum of PUE‐80. This observation indicates that PUE‐80 has larger average crystallite size than other samples according to Scherrer equation . The slight difference could be explained by the crosslink density and interaction of molecular chains.…”
Section: Resultsmentioning
confidence: 79%
“…A narrower half‐breadth at 2 θ = 20° could be observed in diffraction spectrum of PUE‐80. This observation indicates that PUE‐80 has larger average crystallite size than other samples according to Scherrer equation . The slight difference could be explained by the crosslink density and interaction of molecular chains.…”
Section: Resultsmentioning
confidence: 79%
“…Cullity and Stock 38 showed that the Scherrer’s equation is valid only for crystallite sizes up to 200 nm and has close relation to the resolution of the diffractometers. According to Miranda and Sasaki 39 in an X-ray diffraction pattern, there is a multiple scattering, the waves scattered by one atom (or atomic plane) are also scattered by the other atoms (or atomic planes) and those waves are also subsequently scattered by other atoms and so on. The limits of the Scherrer’s equation have been described by Muniz et al .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high potential error in particle size determination via Scherrer analysis, 39 TEM was used to further explore particle size and morphology, as shown in Figure 2. § § An average particle size of 28 ± 19 nm was calculated for 1, based on statistical analysis, with a wide distribution (10 nm to 89 nm).…”
Section: Effect Of Ssm Procedures On Sco Propertiesmentioning
confidence: 99%